Impedance data interpretation for a modified LSCF via distribution of relaxation times analyses - Safian, Suhaida Dila; Malik, Lidyayatty; Osman, Nafisah (Faculty of Applied Sciences, 2025)
Lanthanum Strontium Cobalt Ferrite Oxide (LSCF) is a cathode material for intermediate-temperature solid oxide fuel cells operating from 500 to 800 °C. To enhance the cathode's performance, it is essential to comprehend the electrochemical behavior, which is frequently analyzed using complex nonlinear least-squares (CNLS) analysis. Nevertheless, this analysis demonstrates certain constraints in the detailed interpretation of the electrochemical processes, particularly at the electrode-electrolyte interface. The distribution of relaxation times (DRT) is supportive when deconvoluting complex impedance spectra and has gained increased attention. Hence, this study is conducted to measure the electrochemical impedance data analyses by CNLS and the DRT of a fabricated modified 25 mm symmetrical cell, mLSCF|BCZY|m-LSCF (m=modified, LSCF = La0.6Sr0.4Co0.2Fe0.8O3 and BCZY = BaCe0.54Zr0.36Y0.1O2.95). In a Nyquist plot, the cell shows depressed semi-circles, representing a few interface processes occur. The DRT analysis reveals the semi-circles consisting of four different sub-processes (represented by four peaks) than CNLS (represented by four impedance arcs). The results show that the area-specific resistance (ASR) values for CNLS were 0.3 Ωcm2 and 0.75 Ωcm2 , with 0.25 Ωcm2 and 0.71 Ω cm2 for DRT analysis.